2011
DOI: 10.1007/s11164-011-0253-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supercritical fluid of CO2 drying during Cu/ZnO catalyst preparation on methanol synthesis from syngas at low temperature

Abstract: A copper-based catalyst can be utilized to synthesize methanol from syngas containing carbon dioxide as well as water at low temperature and low pressure. However, the agglomeration of the metallic copper and zinc oxide decreased the catalyst surface area and the Cu-specific surface area. In order to prevent the sintering, the supercritical CO 2 was used to extract water from the catalyst precursor. Our results demonstrate that the Cu-specific surface area was the essential factor to affect the catalytic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It was found that the precursor experienced significant sintering during drying [38]. To overcome this problem, Meng [53] proposed the use of supercritical CO 2 (SC-CO 2 ) to extract the solvent from the catalyst precursor to avoid agglomeration of the catalyst structure. The Cu/ZnO catalyst prepared by SC-CO 2 drying method showed excellent performance for methanol synthesis from syngas compared to the conventional Cu/ ZnO catalyst.…”
Section: Effect Of Catalyst Preparation Methodsmentioning
confidence: 99%
“…It was found that the precursor experienced significant sintering during drying [38]. To overcome this problem, Meng [53] proposed the use of supercritical CO 2 (SC-CO 2 ) to extract the solvent from the catalyst precursor to avoid agglomeration of the catalyst structure. The Cu/ZnO catalyst prepared by SC-CO 2 drying method showed excellent performance for methanol synthesis from syngas compared to the conventional Cu/ ZnO catalyst.…”
Section: Effect Of Catalyst Preparation Methodsmentioning
confidence: 99%
“…A Cu/Zn molar ratio of 1 was observed to be the best for methanol production. This ratio was also applied in most of the related studies. ,, To improve the methanol yield, Tsubaki and co-workers employed a supercritical CO 2 -drying method during the catalyst preparation procedure, which allowed the extraction of water under mild conditions, maintaining the structure of catalyst precursors. As a result, the Cu dispersion was improved and hence the methanol yield increased.…”
Section: Applications Beyond Traditional Synthesis and Productionsmentioning
confidence: 99%
“…20,[29][30][31][32][33][34][35] Among them, Cu-ZnO based catalysts have shown the highest efficiency in terms of yield and cost. [36][37][38] In the Cu-ZnO based catalyst, H 2 dissociation occurs on the metallic copper site and CO 2 is adsorbed on the metal oxide sites, i.e., ZnO or ZrO 2 . 39 For the methanol synthesis reaction, the rate-limiting step is the intermediate formation reaction on metal oxides (ZnO or ZrO 2 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…20,29–35 Among them, Cu–ZnO based catalysts have shown the highest efficiency in terms of yield and cost. 36–38 In the Cu–ZnO based catalyst, H 2 dissociation occurs on the metallic copper site and CO 2 is adsorbed on the metal oxide sites, i.e. , ZnO or ZrO 2 .…”
Section: Introductionmentioning
confidence: 99%